Răspuns :
Răspuns:
Explicație pas cu pas:
a)
[tex]\displaystyle (1-\frac{19}{20} )\times (-5)+\frac{13}{4} =(\frac{20}{20} -\frac{19}{20} )\times (-5) +\frac{13}{4} =\frac{1}{\not20} \times (\not-5) +\frac{13}{4} =-\frac{1}{4} +\frac{13}{4} =\frac{12}{4} =3[/tex]
b)
[tex]\displaystyle \frac{2}{7} -(1-\frac{5}{7} )\times (\frac{13}{2} -\frac{3}{4} )=\frac{2}{7} -(\frac{7}{7} -\frac{5}{7} )\times (\frac{26}{4} -\frac{3}{4} )=\frac{2}{7} -\frac{\not2}{7} \times \frac{23}{\not4} =\frac{2}{7} -\frac{23}{14} =\frac{4}{14} -\frac{23}{14} =-\frac{19}{14}[/tex]
c)
[tex]\displaystyle 2 \times (\frac{5}{\frac{-1}{3} } )-(\frac{2}{7} )^2\times\frac{14}{3} =2 \times (-15)-\frac{4}{\not49} \times\frac{\not14}{3} =-30-\frac{8}{21} =-\frac{630}{21} -\frac{8}{21} =-\frac{638}{21}[/tex]
d)
[tex]\displaystyle 2\times [5-\frac{5}{8} \times (\frac{1}{3} -\frac{3}{5} )]=2\times[5-\frac{5}{8} \times (\frac{5}{15} -\frac{9}{15} )]=2\times[5-\frac{5}{8} \times (-\frac{4}{15} )]=2\times (5+\frac{1}{6} )=2\times(\frac{30}{6} -\frac{1}{6} )=\not2\times \frac{29}{\not6} =\frac{29}{3}[/tex]
e)
[tex]\displaystyle \frac{1}{4} :[\frac{5}{4} -\frac{2}{3} \times(1,5 -0,75)]=\frac{1}{4} :[\frac{5}{4} -\frac{2}{3} \times0,75]=\frac{1}{4} :[\frac{5}{4} -\frac{2}{3} \times\frac{\not75}{\not100} ]=\frac{1}{4} :[\frac{5}{4} -\frac{2}{\not3} \times \frac{\not3}{4} ]=\frac{1}{4} :[\frac{5}{4} -\frac{2}{4} ]=\frac{1}{4} :\frac{3}{4} =\frac{1}{\not4} \times \frac{\not4}{3} =\frac{1}{3}[/tex]
f)
[tex]\displaystyle [1(\frac{3}{5} )^2:(\frac{3}{5} )^4]:\frac{5}{13} =[1\frac{9}{25} :\frac{81}{625} ]\times\frac{13}{5} =\frac{34}{25} \times\frac{\not625}{81} \times\frac{13}{\not5} =\frac{34}{\not25} \times\frac{\not125}{81} \times 13=34\times\frac{5}{81} \times 13=\frac{2210}{81}[/tex]